2020
DOI: 10.1186/s12967-020-02442-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the registered clinical trials for coronavirus disease 2019 (COVID-19)

Abstract: Background Since the outbreak of coronavirus disease 2019 (COVID-19), many researchers in China have performed related clinical research. However, systematic reviews of the registered clinical trials are still lacking. Therefore, we conducted a systematic review of clinical trials for COVID-19 to summarize their characteristics. Methods This study is based on the PRISMA recommendations in the Cochrane handbook. The Chinese Clinical Registration Center and the ClinicalTrials.gov databases were searched to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…The race to find a treatment of this deadly viral infectious disease has started all over the world [105] , [106] , [107] . More than one thousand trials of various synthetic small molecules, natural molecules, antibodies, or vaccines are under progress in search of effective treatment against this deadly disease (clinicaltrials.gov) [108] , [109] , [110] , [111] . Most synthetic small molecules under clinical trials are repurposed for COVID-19 which are already reported for their efficiency against other disease states ( Table 2 , Fig.…”
Section: Different Repurposed Drug Molecules Under Clinical Trials Agmentioning
confidence: 99%
“…The race to find a treatment of this deadly viral infectious disease has started all over the world [105] , [106] , [107] . More than one thousand trials of various synthetic small molecules, natural molecules, antibodies, or vaccines are under progress in search of effective treatment against this deadly disease (clinicaltrials.gov) [108] , [109] , [110] , [111] . Most synthetic small molecules under clinical trials are repurposed for COVID-19 which are already reported for their efficiency against other disease states ( Table 2 , Fig.…”
Section: Different Repurposed Drug Molecules Under Clinical Trials Agmentioning
confidence: 99%
“…COVID-19 spreads fast among people and the mortality rate is controversial; however, it was less than 2% in some studies. The main manifestations of the disease include fever, dry caught, headache, shortness of breath, pneumonia, acute respiratory distress syndrome (ARDS), septic shock, and even death [3,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is no licensed treatment or approved vaccine and the number of new cases and mortality multiplies daily [8]. Therefore, it is vital to develop an effective treatment strategy to control the virus spread and prevent the disease [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…On December 31, 2019, the World Health Organization (WHO) China Country Office was informed of pneumonia cases of unknown etiology 1 ; on January 30, 2020, the WHO declared coronavirus disease 2019 (COVID-19) 2 a public health emergency and on March 11 a pandemic 3 . Radical public health measures, including quarantine, social distancing, school and workplace closures, and others have been implemented worldwide, affecting the lives of billions of people.…”
Section: Introductionmentioning
confidence: 99%